Upaya Dinas Pendidikan Kota Semarang dalam Implementasi Kebijakan Pendidikan Penguatan Karakter (PPK) Tingkat Sekolah Menengah Pertama (SMP) di Kota Semarang - Meutia Pelangi Hapsari; Nunik Retno Herawati (Journal of Politic and Government Studies, 2018)
Education is essentially a human conscious effort to develop the personality both inside out of school and last a lifetime. Educational reform is a response to the development of global demands as attempt to adapt an educational system which is capable of developing human resources to meet the demands of the emerging era. Seeing the condition of the problems of the nation’s generation in this globalization era is quite apprehensive so many case concern education recently until becoming viral in Indonesia. Character education is a very important key in making the child’s personality. In addition to home, character education also need to be applied at school and social environment. The issued raised in this study; what is the Role of the Education Office in Semarang City in the Implementatation of Character Building Education Policy.The purpose and research is to know how the Role of the Education Office in Semarang City in the Implementation of Character Building Education Policy.The method which is used in this research is qualitative method by doing data collection tevhniques such as interview, observation and documentation. The informants in this study is the leadership of the Education Office of Semarang City, employees and supervisors. The result of this study indicate that the Role of the Education Office of Semarang City in the implementation of the Character Building Education policy has been running well. The main problem faced is about human resources and facilities.Keywords: Public Policy, Character Education, Implementation